Systolic Blood Pressure and 1-Year Clinical Outcomes in Patients Hospitalized for Heart Failure - Huang, Xinghe; Liu, Jiamin; Zhang, Lihua; Wang, Bin; Bai, Xueke; Hu, Shuang; Miao, Fengyu; Tian, Aoxi; Yang, Tingxuan; Li, Yan; Li, Jing (Frontiers in Cardiovascular Medicine, 2022)
Background: High systolic blood pressure (SBP) is an important risk factor for progression of heart failure (HF); however, the association between SBP and prognosis among patients with established HF was uncertain. This study aimed to investigate the association between SBP and long-term clinical outcomes in patients hospitalized for HF. Methods: This study prospectively enrolled adult patients hospitalized for HF in 52 hospitals from 20 provinces in China. SBPs were measured in a stable condition judged by clinicians during hospitalization before discharge according to the standard research protocol. The primary outcomes included one-year all-cause death and HF readmission. The multivariable Cox proportional hazards regression models were fitted to examine the association between SBP and clinical outcomes. Restricted cubic splines were used to examine the nonlinear associations. Results: The 4564 patients had a mean age of 65.3±13.5 years and 37.9% were female. The average SBP was 123.2±19.0 mmHg. One-year all-cause death and HF readmission were 16.9% and 32.7%, respectively. After adjustment, patients with SBP <110 mmHg had a higher risk of all-cause death compared to those with SBP of 130-139 mmHg (HR 1.71; 95% CI: 1.32-2.20). Patients with SBP <110 mmHg (HR 1.36; 95% CI: 1.14-1.64) and SBP >=150 mmHg (HR 1.26; 95% CI: 1.01-1.58) had a higher risk of HF readmission, and the association between SBP and HF readmission followed a J-curve relationship with the nadir SBP around 130 mmHg. These associations were consistent regardless of age, sex, left ventricular ejection fraction, hypertension, coronary heart disease, and medications for HF. Conclusions: In patients hospitalized for HF, lower SBP in a stable phase during hospitalization portends an increased risk of one-year death, and a J curve association has been observed between SBP and one-year HF readmission. These associations were consistent among clinically important subgroups.